Pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Tirtakencana Tatawarna Karawang - Chandra Firmansyah; Tridays Repelita; Luthfi Fairuzi Nurhafiz; Anandia Shafira; Mohammad Kamil (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to analyze the influence of the work environment and job satisfaction on employee performance at PT Tirtakencana Tatawarna in Karawang. The study employed a qualitative approach with descriptive methods to gain an in-depth understanding of employee perceptions and experiences regarding their working conditions. Informants were selected using purposive sampling, with the criteria being employees who had worked for at least one year and were directly involved in the company's operational activities. Data collection was conducted through in-depth interviews supported by documentation studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity tested using source triangulation. The results indicate that a conducive work environment, both physical and non-physical, and a good level of job satisfaction have a positive effect on employee performance. A comfortable work environment and harmonious working relationships can increase employee motivation and effectiveness, while job satisfaction fosters a positive attitude and responsibility in completing tasks. Thus, the work environment and job satisfaction play a significant role in improving employee performance at PT Tirtakencana Tatawarna in Karawang.